Reconnoitring the association of nutritional status with oral health in elementary school-going children of Ghaziabad City, North India - Shveta Sood; Vipin Ahuja; Swati Chowdhry (Wolters Kluwer Medknow Publications, 2014)
Purpose: The purpose of this study was to evaluate the association between anthropometric measurements and oral health status in the primary dentition of school-going children. Materials and Methods: In this study, 280 elementary school children (116 girls and 164 boys, age: 3-6 years) were examined. Body mass index (BMI) of each subject was calculated and compared with age and gender using Centers for Disease Control and Prevention (CDC) pediatric growth charts. Based on these growth charts, the sample population was distributed into three groups: Group I: Normal weight (5 th -85 th percentiles), Group II: Risk of overweight/obese (>85 th percentile), and Group III: Underweight (<5 th percentile). Each subject was examined for caries frequency (decayed and filled primary teeth (dft) values) and plaque status (plaque index (PI)) and these values were compared with their BMI figures. Results: Among the study group, 58.3% of children were suffering from malnutrition. Out of the total population, 33.9% had caries affecting their primary dentition. The largest section (39.5%) of caries affected children was underweight. The mean number of dft in Group II was highest at 1.47 ± 2.77 followed by Groups I and III, respectively. The mean value of PI in Group III was highest at 0.33 ± 0.53 followed by Groups II and I. Conclusions: A definite correlation was observed between the oral health status and BMI of elementary school-going children.